Development of e-learning application prototype for dynamic ecosystem based on ARCS motivational design model / Nor Imrah Abdul Rahim - Abdul Rahim, Nor Imrah (2011)
Distance education is rapidly becoming an increasingly important - and even preferred - method of instructional delivery for many educational contexts. In spite of the many student benefits surrounding distance learning programs, however, a great number of distance learning courses suffer from extremely low student completion rates when compared to their traditional classroom-based counterparts. Although it may be tempting to point to instructional content and methods as the source of low distance learning completion rates, it can be shown that it is often motivational problems, and not the instruction itself, which lay at the root of these statistics. Motivation to learn is paramount to student success; however, the sources of motivation are complex. This paper examines internal and external factors that influence the motivation to learn, as well as the principles of motivation as applied to instructional design. ARCS Motivational Design Model points out that instructional process are required to be configured with the strategies which increase the attention, relevance, confidence and satisfaction of the students for an instructional design which ensures the continuity of learning motivation.